2017
DOI: 10.1111/jdv.14384
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab substantially improves dermatology‐related quality of life in patients with chronic spontaneous urticaria

Abstract: BackgroundChronic spontaneous/idiopathic urticaria (CSU/CIU) has substantial detrimental effects on health‐related quality of life (HRQoL) with an effect comparable to or worse than many other skin diseases.ObjectiveTo assess the effect of omalizumab on CSU patients' HRQoL, measured by the Dermatology Life Quality Index (DLQI) in three phase III studies ASTERIA I, ASTERIA II and GLACIAL.MethodsA post hoc analysis examined changes in DLQI scores, distribution of patients across DLQI bands and the proportion rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 26 publications
3
22
0
6
Order By: Relevance
“…Similarly, the mean change in DLQI in our study group was −7.5 at third month. The proportion of the patients achieving the MCID of 4 points or more in DLQI-total score at Week 12 was 74.1-77.1% in previous studies, accordingly 69% of our study group reached the MCID or more at Week 12 (Finlay et al, 2017). Accordingly with our results, the improvement in DLQI subscales was significantly better compared to placebo group (Finlay et al, 2017;Staubach et al, 2018), except for personal relationships subscale was not different from placebo group in one study (Finlay et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, the mean change in DLQI in our study group was −7.5 at third month. The proportion of the patients achieving the MCID of 4 points or more in DLQI-total score at Week 12 was 74.1-77.1% in previous studies, accordingly 69% of our study group reached the MCID or more at Week 12 (Finlay et al, 2017). Accordingly with our results, the improvement in DLQI subscales was significantly better compared to placebo group (Finlay et al, 2017;Staubach et al, 2018), except for personal relationships subscale was not different from placebo group in one study (Finlay et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…2017; Staubach et al, 2018). A mean decrease of 4.49-10.3 points in DLQI-total has been reported at Week 12 (Finlay et al, 2017;Maurer, Sofen, et al, 2017). Similarly, the mean change in DLQI in our study group was −7.5 at third month.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, angioedema in CSU should prompt adequate treatment. The development of new treatments specifically for CSU has been shown to prevent angioedema and improve angioedema‐dependent and dermatology‐related quality of life . Future research should explore the clinical course of angioedema in CSU—including the most commonly affected areas, the clinical differences compared with hereditary angioedema and evolution of symptoms over time—as well as the distinct management patterns that patients with angioedema in CSU require.…”
Section: Discussionmentioning
confidence: 99%
“…2 Clinical trials have shown that treatment with omalizumab is effective on urticaria symptoms and disease-related quality of life and also reduces the need for additional medication. [2][3][4][5][6][7][8][9][10] Out-oftrial data have shown that approximately 65% of patients with CSU report complete response to omalizumab, while 25% obtain partial response and around 15% have no or very limited response. 11 However, prospective data on real-life response to omalizumab in CSU are still lacking.…”
Section: Introductionmentioning
confidence: 99%